Clinicopathologic and genetic features of multiple system atrophy with Lewy body disease. (14th April 2020) - Koga, Shunsuke; Li, Fuyao; Zhao, Na; Roemer, Shanu F.; Ferman, Tanis J.; Wernick, Anna I.; Walton, Ronald L.; Faroqi, Ayman H.; Graff‐Radford, Neill R.; Cheshire, William P.; Ross, Owen A.; Dickson, Dennis W.
Abstract: Background: Abnormal aggregates of α‐synuclein are pathologic hallmarks of multiple system atrophy (MSA) and Lewy body disease (LBD). LBD sometimes coexists with MSA, but the impact of co‐pathology, particularly diffuse LBD, on presentation of MSA has not been studied. We aimed to determine the frequency and clinicopathologic features of MSA with LBD (MSA+LBD). Methods: Using hematoxylin & eosin and α‐synuclein‐immunostained slides, we assessed the distribution and severity of LBD in 230 autopsy‐confirmed MSA patients collected from 1998 to 2018. Alzheimer‐type pathology was assessed to assign the likelihood of clinical presentations of dementia with Lewy body (DLB) using the consensus criteria for DLB. We reviewed medical records to characterize clinicopathologic features of MSA+LBD. Genetic risk factors for LBD, including APOE ε4 allele and mutations in GBA, SNCA, LRRK2, and VPS35, were analyzed. Results: LBD was observed in 11 MSA patients (5%); seven were brainstem type, three were transitional type, and one was diffuse type. The latter four had an intermediate or high likelihood of DLB. Three of the four had an antemortem diagnosis of Parkinson's disease with dementia (PDD) or clinically probable DLB. Two patients had neuronal loss in the substantia nigra, but not in striatal or olivocerebellar systems with widespread glial cytoplasmic inclusions, consistent with minimal change MSA. In these cases, LBD was considered the primary pathology, and MSA was considered coincidental. APOE ε4 allele frequency was not different between MSA+LBD and MSA without LBD. Two of nine MSA+LBD patients had a risk variant of GBA (p.T408M and p.E365K). Conclusions: Although rare, MSA with transitional or diffuse LBD can develop clinical features of PDD or DLB. Minimal change MSA can be interpreted as a coincidental, but distinct, α‐synucleinopathy in a subset of patients with diffuse LBD.